THE INFLUENCE OF SIZE UPPER ARM CIRCUMFERENCE (LLA) THIRD TRIMESTER PREGNANT WOMEN ON THE BIRTH WEIGHT BABIES IN BPS SITI SUJALMI JATINOM KLATEN - Trilies Pancesih Qobadiyah; Musta'in .; Maryanti . (STIKES DUTAGAMA KLATEN, 2012)
Background: The incidence of BBLR in Indonesia ranges between 9% - 30%. BBLR caused by poor nutrition status of mothers at risk Lack of Energy Calories (KEK). Nutritional status of pregnant women can be measured anthropometry / body composition measurements by measuring LLA (Upper Arm Circumference), called KEK when LLA is less than 23,5 cm. LLA is the dominant factor on the risk of Low Birth Weight Babies (BBLR). Based on the results of preliminary studies in BPS Siti Sujalmi there are 2 third trimester pregnant women who have the LLA < 23,5 cm and low birth weight babies as many as seven of 292 cases of birth in January to November of 2011. Purpose: This study aims to determine the effect of the size of Upper Arm Circumference (LLA) third trimester pregnant women on birth weight babies in the BPS Siti Sujalmi Jatinom Klaten. Research Methods: The study is a kind of analytic survey research with case control design with a retrospective approach. The population in this study were all pregnant women who do the third trimester antenatal and childbirth in the BPS Siti Sujalmi Jatinom Klaten in May-June 2012. Sampling techniques in total sampling, a sample of 49 people. Data analysis using the Spearman Rank correlation statistical tests with SPSS version 17. Results: The results of the research prove that there is effect of upper arm circumference third trimester pregnant women on birth weight babies as indicated by 40% of 10 third trimester pregnant mother who have size of Upper Arm Circumference is less than 23,5 cm childbirth babies with weight less than 2500 gram (low birth weight). The results are so indicated by the count value of ρ = 0,529 and ρ the table at the level of error of 5% (0,364). Influence is strong enough indicated by the value of the correlation coefficient of 0,529 is based on the closeness of the relationship between the variables table, the value indicates a strong enough relation category. Conclusion: The LLA size of third trimester pregnant women has a strong enough influence on birth weight babies at BPS Siti Sujalmi Jatinom Klaten.